An endoplasmic reticulum protein, Nogo‐B, facilitates alcoholic liver disease through regulation of kupffer cell polarization. Issue 5 (22nd March 2017) - Park, Jin‐Kyu; Shao, Mingjie; Kim, Moon Young; Baik, Soon Koo; Cho, Mee Yon; Utsumi, Teruo; Satoh, Ayano; Ouyang, Xinsho; Chung, Chuhan; Iwakiri, Yasuko
Abstract : Nogo‐B (Reticulon 4B) is an endoplasmic reticulum (ER) resident protein that regulates ER structure and function. Because ER stress is known to induce M2 macrophage polarization, we examined whether Nogo‐B regulates M1/M2 polarization of Kupffer cells and alters the pathogenesis of alcoholic liver disease (ALD). M1 and M2 phenotypes were assessed in relation to Nogo‐B expression and disease severity in liver specimens from ALD patients (NCT01875211). Liver specimens from wild‐type (WT) and Nogo‐B knockout (KO) mice fed a control or Lieber‐DeCarli ethanol liquid diet (5% ethanol) for 6 weeks were analyzed for liver injury and steatosis. Kupffer cells isolated from WT and Nogo‐B KO mice were assessed for M1 and M2 activation. A significant positive correlation was observed between Nogo‐B positive Kupffer cells and disease severity in ALD patients (n = 30, r = 0.66, P = 0.048). Furthermore, Nogo‐B–positive Kupffer cells were correlated with M1 activation (inducible nitric oxide synthase) ( r = 0.50, P = 0.05) and negatively with markers of M2 status (CD163) ( r = −0.48, P = 0.07) in these patients. WT mice exhibited significantly increased liver injury ( P < 0.05) and higher hepatic triglyceride levels ( P < 0.01) compared with Nogo‐B KO mice in response to chronic ethanol feeding. Nogo‐B in Kupffer cells promoted M1 polarization, whereas absence of Nogo‐B increased ER stress and M2 polarization in Kupffer cells. Conclusion : Nogo‐B is permissive of M1 polarization of Kupffer cells, thereby accentuating liver injury in ALD in humans and mice. Nogo‐B in Kupffer cells may represent a new therapeutic target for ALD. (Hepatology 2017;65:1720‐1734).